2020
DOI: 10.3390/microorganisms8010071
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the 1-Aminocyclopropane-1-Carboxylate Metabolic Rate of Pseudomonas sp. UW4 Intensifies Chemotactic Rhizocompetence

Abstract: 1-aminocyclopropane-1-carboxylic acid (ACC) is a strong metabolism-dependent chemoattractant for the plant beneficial rhizobacterium Pseudomonas sp. UW4. It is unknown whether enhancing the metabolic rate of ACC can intensify the chemotaxis activity towards ACC and rhizocompetence. In this study, we selected four promoters to transcribe the UW4 ACC deaminase (AcdS) gene in the UW4 ΔAcdS mutant. PA is the UW4 AcdS gene promoter, PB20, PB10 and PB1 are synthetic promoters. The order of the AcdS gene expression l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Because of this inherent characteristic, ACC deaminase synthesis is a fascinating and promising option for crop development. Similarly to this, ACC deaminase producing rhizobacterial strains such as Bacillus ( Gowtham et al., 2020 ) and Pseudomonas ( Gao et al., 2020 ) have been reported.…”
Section: Resultsmentioning
confidence: 52%
“…Because of this inherent characteristic, ACC deaminase synthesis is a fascinating and promising option for crop development. Similarly to this, ACC deaminase producing rhizobacterial strains such as Bacillus ( Gowtham et al., 2020 ) and Pseudomonas ( Gao et al., 2020 ) have been reported.…”
Section: Resultsmentioning
confidence: 52%
“…The 1-amino cyclopropane 1-carboxylate (ACC) deaminase produced by a variety of plant-beneficial soil microorganisms is another exceptional biological characteristic that may significantly reduce the ethylene levels in plants and, hence, speed up the functioning of growing plants under harsher environments (Gao et al, 2020 ; Jha et al, 2021 ). Here, even when grown in media supplemented with different levels (0, 2, 5, 7, 10, 12, and 15%) of NaCl, strain KR-17 showed a favorable response to ACC deaminase.…”
Section: Resultsmentioning
confidence: 99%
“…UW4 which increased the bacterial ability to colonize the rhizosphere and stimulate the growth of wheat plants. The authors of that study concluded that ACC which was produced and excreted by the plant can be a very powerful chemoattractant for microbial strains with high levels of ACC deaminase activity [ 100 ]. This study is consistent with the work of Moon and Ali [ 99 ] mentioned above as well as a model of ACC deaminase functioning postulated earlier [ 90 ].…”
Section: Ethylenementioning
confidence: 99%